Transforming ownership and governance - Lessons from capital intensive pelagic fisheries in South Africa and Zimbabwe - Kefasi Nyikahadzoi; Mafaniso Hara; Jesper Raakjær (International Journal of the Commons, 2010)
This article is on the political economy of transformation and governance reform in industrial fisheries in Southern African states undergoing political and socio-economic transformation. Specifically, it focuses on the experiences of transformation and reform of governance in the pelagic fisheries of South Africa and Zimbabwe. A democratic South Africa and independent Zimbabwe each inherited a dual socio-economic system characterised by racially based inequitable distribution of political and economic powers, and productive assets in favour of the white minority. This study provides a comparative analysis of the driving forces for transformation and governance reform in the two countries. The study demonstrates that reliance on market mechanisms as the main driving force for change in both countries has merely reinforced the existing ownership patterns and power relations, with a limited number of strategically positioned black elites benefiting. Neither the state nor the market place has been able to secure equitable distribution and the creation of an inclusive governance system. Instead disputes are often still settled in courts. This paper concludes that the solution could be found in innovative approaches to transformation and governance that genuinely include the players without undermining the economic viability of the industry rather than the use of conventional top-down state and free market interventions.